Confirmatory factor analysis (CFA) and psychometric validation of healthy lifestyle and personal control questionnaire (HLPCQ) in India - Himani Goyal; Sheema Aleem (Wolters Kluwer Medknow Publications, 2023)
Background: The silent epidemic of chronic illness has become a significant public health challenge worldwide. The prevention and management of these deadliest health conditions primarily require empowering the individual to make healthy choices every day, e.g., healthy eating, physical exercise, etc., The first step in designing an intervention for this comprises measuring the health empowerment-related factor. However, severe scarcity of practical tools is noted. Objective: The present study aimed at the evaluation of psychometric properties of a healthy lifestyle and personal control questionnaire (HLPCQ)'s English Version in the Indian population. Method: For this, a cross-sectional study was conducted on 618 people enlisted from the Northern state of India with the help of convenience sampling strategy. Data is collected by sharing the google form of HLPCQ through various online platforms. Results: The value of Cronbach alpha and MacDonald's Omega, was >.70, suggesting HLPCQ has good reliability in the Indian population. While confirmatory factor analysis result shows that the final model with 24 items has a good fit to the data (RMSEA = 0.04, CFI = 0.97, TLI = 0.96, SRMR = 0.03) which implies that HLPCQ has acceptable structural and cultural validity. While the value of average variance extracted (AVE) and composite reliability (CR) for each factor were found to be more than .50 and .70 respectively, indicating the presence of convergent and discriminant validity for HLPCQ. Conclusion: These findings indicate that the HLPCQ has sound psychometric properties and can be used in the Indian population.